The Origin of The Basic Formula of The Fourier Series - Wikaria Gazali (Bina Nusantara University, 2023)
This paper discusses the Origin of the Basic Formula for the Fourier Series f(t)=a0/2+∑∞k=1 [ak cos⁡(kπt/L)+bk sin⁡(kπt/L) ] To obtain this model, the author derives the basic formula for the Fourier Series from Elementary Linear Algebra. In this derivation, we use the best approximation: least squares method whose details will be elaborated in this paper until we obtain the formula for the Fourier Series.